Pengaruh Implementasi Total Quality Management pada Kinerja Manajerial Perusahaan Otobus Pariwisata di Kota Denpasar - Tri Bhuwana Dewi, I Gusti Ayu; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
Total Quality Management (TQM) is a modern management concept that seeks to provide an appropriate response to existing changes. The purpose of this study was to determine the effect of aspects on TQM, namely focus on customers, obsession with quality, continuous improvement and employee involvement and empowerment on the managerial performance of tourism OC. Respondents in this study were all employees of 8 tourism otobus companies in Denpasar that were determined by the non-probability sampling method, namely saturated sampling. Data collection is done by questionnaire with data analysis techniques, namely multiple linear regression. Based on the results of the analysis shows aspects of TQM namely customer focus, obsession with quality, continuous improvement and employee involvement and empowerment have a positive and significant effect on managerial performance on tourism OCs in Denpasar. Keywords: Organizational Theory; Total Quality Management; Managerial Performance.